The Influence of Audit Quality, Accounting Conservatism, Financial Distress, and Leverage on Tax Avoidance in Banking Sub-Sector Companies Listed - epergamus simarmata; Keri Boru Hotang; Lembah Dewi Andini (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2025)
Abstract Purpose - This study aims to obtain empirical evidence about the effect of audit quality, accounting conservatism, financial distress, and leverage on tax avoidance Design/methodology/approach: This research uses quantitative research. The sample of this study used a sample of bank sub-sector companies listed on the Indonesia Stock Exchange in 2017 - 2023. Sample selection based on certain criteria using purposive sampling method. The data used in the study was 98 observation data from companies in 7 reporting years. The analysis technique used to test the hypothesis is multiple linear analysis using EViews 9 software. Findings: The results of this study found that Audit Quality has a negative and statistically insignificant effect on Tax Avoidance. While Accounting Conservatism has a positive but statistically insignificant effect on Tax Avoidance. Financial Distress has a negative and statistically insignificant effect on Tax Avoidance and Leverage has a positive and statistically significant effect on Tax Avoidance. Research limitations/implications: This study discusses Audit Quality, and other factors such as Accounting Conservatism, Financial Distress, and Leverage which focus on Bank Sub-Sector companies.